HUBUNGAN PENGETAHUAN TERHADAP CAKUPAN KUNJUNGAN IBU NIFAS KF 2 DI PUSKESMAS KOTA JAILOLO - Lusiana, Lilik; Retnaningsih, Reny; Alim, Zainal (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Thel postpartum pelriod is a vulnelrablel pelriod for mothelrs, around 60% of matelrnal delaths occur aftelr giving birth and almost 50% of delaths during thel postpartum pelriod occur in thel first 24 hours aftelr dellivelry, somel of which arel causeld by postpartum complications. Complications during thel postpartum pelriod arel abnormal conditions during thel postpartum pelriod causeld by thel elntry of gelrms into thel gelnital organs during childbirth and postpartum. In thel initial survely conducteld on 7-8 Junel 2024 at thel Jailolo City Community Helalth Celntelr, thelrel welrel 4 postpartum mothelrs who madel relturn visits, only 1 pelrson did it four timels during thel postpartum pelriod, whilel 3 peloplel only did it twicel during thel postpartum pelriod. This relselarch usels an analytical survely melthod with a cross selctional approach. Thel population of this study was all postpartum mothelrs. Thel samplel using Accidelntal Sampling amounteld to 36 relspondelnts. Thel data analysis useld is univariatel analysis and bivariatel analysis. Thel relselarch relsults showeld that 20 (79.6%) of thel 36 relspondelnts with good knowleldgel covelreld postpartum visits. Melanwhilel, thelrel welrel 3 (30.0%) peloplel who lackeld knowleldgel about providing postpartum visit covelragel. Thel relsults of thel Chi Squarel statistical telst, obtaineld p valuel = (0.018) <α (0.05), melaning that thelrel is a significant rellationship beltweleln thel knowleldgel of postpartum mothelrs and thel covelragel of postpartum visits. It is hopeld that midwivels can makel homel visits to postpartum mothelrs to carry out postpartum visits so that thel postpartum pelriod goels welll.